Implementation of The Staged Self-Directed Learning Model in The Creation of Distance Student Entrepreneurship Competition About Blue Ocean Strategy - Maria M. SIMCHUK; Diana YURKOVLYANETS; Anastasii I. KLIMIN; Sergey V. SALKUTSAN (Communications of International Proceedings, 2020)
The article aims at presenting the reader with a proposal of implementation of the Blue Ocean Strategy and The Staged Self-Directed Learning Model (SSDL) in higher education distance programs in order to provide students an environment where they can obtain skills necessary for their future career.  First, the reasons why students of all specialties are in need of acquiring basic entrepreneurial skills by creating innovative projects and startups, using Blue Ocean Strategy, are provided. Second, the challenges of transforming the educational process in higher education due to meeting the needs of Generation Z’ students will be discussed. Third, the implementation of the Staged Self-Directed Learning Model will be proposed in order to create a convenient learning environment for modern students using distance teaching methods and new ways of communication via social networks. Fourth, the results of pilot implementation of this method of creating distance learning process in “The Blue Ocean Open Polytech Entrepreneurship Competition” in the Saint Petersburg Polytechnic University of Peter the Great with the support of The Russian-German Center for Innovation and Entrepreneurship “Polytech Strascheg” and Graduate School of Technology Entrepreneurship will be discussed by the way of analyzing online questionnaire with 120 responses with the purpose of measuring effectiveness of distance learning process created with the use of the SSDL model.
Keywords: The Staged Self-Directed Learning Model; Blue Ocean Strategy; eLearning.